2011
DOI: 10.2113/gsjfr.41.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Impact on Benthic Foraminifera, Abu-Qir Bay, Alexandria, Egypt

Abstract: The present study examines the foraminiferal distribution in recent bottom sediments of Abu-Qir Bay located along the Mediterranean coast of Alexandria, Egypt. Abu-Qir Bay receives substantial amounts of heavy metals from the surrounding industrial area, as well as agricultural and domestic effluents, which makes it one of the most polluted areas along the Mediterranean coast. Information provided by the benthic foraminiferal associations was integrated with geochemical, sedimentological, and water data to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 75 publications
1
20
1
1
Order By: Relevance
“…Conversely, at polluted sites, organic supplies are usually accompanied by a more or less wide range of toxic chemical compounds, and the faunas potentially show a response to a multiple stressor context. In many cases of anthropogenic pollution there is a positive correlation between TOC and the concentrations of chemical pollutants (e.g., Romano et al, 2009Romano et al, , 2013 and by Elshanawany et al, 2011), and TOC values can be used as an integrative descriptor of pollution. However, in some studies, the correlation between TOC and other pollutants is much less evident (e.g., Samir and El-Din, 2001), and TOC may not be a good descriptor for ecosystem stress.…”
Section: Comparing Naturally Eutrophicated and Polluted Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, at polluted sites, organic supplies are usually accompanied by a more or less wide range of toxic chemical compounds, and the faunas potentially show a response to a multiple stressor context. In many cases of anthropogenic pollution there is a positive correlation between TOC and the concentrations of chemical pollutants (e.g., Romano et al, 2009Romano et al, , 2013 and by Elshanawany et al, 2011), and TOC values can be used as an integrative descriptor of pollution. However, in some studies, the correlation between TOC and other pollutants is much less evident (e.g., Samir and El-Din, 2001), and TOC may not be a good descriptor for ecosystem stress.…”
Section: Comparing Naturally Eutrophicated and Polluted Areasmentioning
confidence: 99%
“…In some studies, only very few representatives of Groups III, IV and V were observed. This concerned the studies of Samir and El-Din (2001), Hyams-Kaphzan et al (2008), Romano et al (2009) and Elshanawany et al (2011). These studies apparently did not include heavily organic matter enriched sites.…”
Section: The Master Table Of Ecological Assignmentsmentioning
confidence: 99%
“…Quinqueloculina lata and Quinqueloculina stelligera dominated an area in Naples that was heavily polluted with trace metals . However, other studies assert that the Quinqueloculina genus prefers well-oxygenated environments and is sensitive to heavy metal pollution (e.g., Ferraro et al (2006), Elshanawany et al (2011), Martins et al (2013)). …”
Section: Benthic Foraminifera Responding To Trace Metalsmentioning
confidence: 99%
“…Tekanan antropogenik ini menjadi semakin besar dengan meningkatnya aktivitas manusia di sepanjang pesisir dan atau di sepanjang aliran sungai. Alve (1995), Elshanawany et al (2011), dan Jayaraju et al (2008 menemukan rendahnya keragaman jenis dan adanya cangkang abnormal pada foraminifera bentik di perairan marjinal yang mendapatkan tekanan ekologis akibat aliran bahan antropogenik.…”
Section: Pendahuluanunclassified